An investigation of amount and factors affecting nurses' job stress in some hospitals in Tehran - Rahimi A; Ahmadi F; Akhond MR (Tehran University of Medical Sciences, 2004)
Introduction: Nurses as the main members of treatment-and-care team play an important role in improvement and promotion of health in society. Job stress is a recognized and integral part of modern nursing which has destructive effects on both nurses and patients. Materials and Methods: The present descriptive and analytical study aims to determine the level of nurses' job stress in Tehran in 2004. It also tries to identify factors affecting job stress from nurses' point of view. A total of 111 nurses working in two educational and non-educational hospitals in Tehran were studied. The sampling was simple, i.e. the subjects volunteered to participate in the study. A questionnaire with 2 sections was developed. In the first section we asked about personal and professional characteristics and the second section was designed to evaluate job stress in following 5 categories: management, economy and welfare, mentality and social affairs, occupational health and ergonomics. There was also an open-ended question asking about nurses' attitude toward job stress. The questionnaire items were to be answered on a scale ranging from 0 to 4. We used descriptive statistics and Chi square statistical test to analyze the collected data. Results: The results showed that 44.1% of samples had high levels of job stress while 54.1% suffered from medium and 1.8% from low levels of job stress. There was a significant relationship between hospital type and job stress; job stress in the educational hospital was higher compared to the noneducational hospital. There was also an inverse relationship between years of experience and job stress. Conclusion: Due to high percentage of the subjects with high to medium levels of job stress, employment of preventive and precautionary procedures regarding job stress is recommended.